2005
DOI: 10.1097/01.inf.0000168741.59747.2d
|View full text |Cite
|
Sign up to set email alerts
|

Single Versus Dual Respiratory Virus Infections in Hospitalized Infants

Abstract: The results indicate that the clinical characteristics and the IFN-gamma response differ significantly in single and dual respiratory viral infection, depending on the nature of the simultaneously detected viruses. In dual infections, RSV involvement was associated with a decreased IFN-gamma response in peripheral blood mononuclear cell and an increase in severity of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
8
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(81 citation statements)
references
References 25 publications
9
62
8
2
Order By: Relevance
“…In comparison with children with a sole RSV infection, children with a RSV/RV co-infection had a significantly higher likelihood of bronchiolitis relapse, even after adjusting for many clinical factors and hospital length of stay. Taken together with other data from our group 6 and others, 7,24 our observations challenge the conventional wisdom that the infectious pathogen of severe bronchiolitis does not affect short-term outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In comparison with children with a sole RSV infection, children with a RSV/RV co-infection had a significantly higher likelihood of bronchiolitis relapse, even after adjusting for many clinical factors and hospital length of stay. Taken together with other data from our group 6 and others, 7,24 our observations challenge the conventional wisdom that the infectious pathogen of severe bronchiolitis does not affect short-term outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the clinical significance of multiple pathogen infections remains unclear. 6,24,25 Indeed, the literature has shown that the clinical severity of RSV/RV bronchiolitis is less than, 7 no different than, 10,26 and greater than 6,24 bronchiolitis caused by RSV alone. For example, a single-center study in Greece of 118 children with severe bronchiolitis found that the viral etiologies were not associated with clinical severity score at hospital admission but children with RSV/RV co-infection were hospitalized later in the course of their diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory viral coinfections have been identified in 1.8% - 49.2% of respiratory tract infections in previous studies [1214202728]. The variability in the reported coinfection frequency could be due to the methods of viral detection, the number of detectable viruses, the characteristics of enrolled patients, the frequencies of underlying disorders, the seasons when the studies were performed, and the inclusion or exclusion of URTI [1428].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even as ADV infection occurs steadily all year round in Korea, the clinical impact of respiratory viral coinfection on childhood ADV infection has rarely been reported [19]. In addition, previous studies on ADV coinfections included only children younger than 1 or 3 years of age, or children with lower respiratory tract infections [182021]. This retrospective study was performed to investigate the clinical impact of respiratory viral coinfections in Korean children with ADV infection.…”
Section: Introductionmentioning
confidence: 99%